BIOTREATMENT OF CYANIDE AND TOTAL SUSPENDED SOLIDS (TSS) IN THE GOLD MINE RUNOFF USING LYSINIBACILLUS FUSIFORMIS STRAIN SKC-8 - Rizka Kurniawati, Syafira
Approximately ninety percent of the world's gold extraction is performed using cyanidation at present. Due to the simplicity of applying cyanide to gold ore, the cyanidation method is widely employed in the mining sector and gold ore extraction. In addition, the cyanidation process generates waste that is detrimental to the environment; therefore, the waste from the cyanidation process must undergo a suspended solids sedimentation (TSS) process and cyanide destruction prior to being released into the environment. Industrial procedures typically employ coagulants and flocculants to precipitate TSS and chemical reagents to eliminate cyanide. However, purchasing chemical reagents incurs substantial running expenses. Utilizing the ability of microorganisms, a study was undertaken on alternate reagents to precipitate TSS and eliminate cyanide in metallurgical waste generated from the cyanidation process.